Low-carbon electricity production through the implementation of photovoltaic panels in rooftops in urban environments: A case study for three cities in Peru - Bazán, J.; Rieradevall, J.; Gabarrell i Durany, X.; Vázquez-Rowe, I. (Elsevier, 2018)
Urban environments in Latin America must begin decarbonizing their activities to avoid increasing greenhouse gases (GHGs) emissions rates due to their reliance on fossil fuel-based energy to support economic growth. In this context, cities in Latin America have high potential to convert sunlight into energy. Hence, the main objective of this study was to determine the potential of electricity self-sufficiency production and mitigation of GHG emissions in three medium-sized cities in Peru through the revalorization of underutilized rooftop areas in urban environments. Each city represented a distinct natural area of Peru: Pacific coast, Andean region and Amazon basin. More specifically, photovoltaic solar systems were the technology selected for implementation in these rooftop areas. Data on incident solar energy, temperature and energy consumption were collected. Thereafter, ArcGis10.3 was used to quantify the total usable area in the cities. A series of correction factors, including tilt, orientation or roof profiles were applied to attain an accurate value of usable area. Finally, Life Cycle Assessment was the methodology chosen to calculate the reduction of environmental impacts as compared to the current context of using electricity from the regional grids. Results showed that the cities assessed have the potential to obtain their entire current electricity demand for residential, commercial and public lighting purposes, augmenting energy security and resilience to intermittent natural disasters, with the support of decentralized storage systems. This approach would also translate into substantial reductions in terms of GHG emissions. Annual reductions in GHG emissions ranged from 112 ton CO2eq in the city of Ayacucho to over 523 kton CO2eq in Pucallpa, showing that cities in the Amazon basin would be the ones that benefit the most in terms of climate change mitigation.
Keywords: Photovoltaic system; Electricity; Production (economics); Electricity generation; Carbon fibers; Business; Engineering; Power (physics); Computer science; Economics; https://purl.org/pe-repo/ocde/ford#2.03.04